Characteristics of Parallel and Countercurrent Flooding Instability of Annular Flow in Rod Bundle Channel - JIN Guangyuan1, 2, WANG Rui1, 2, BAI Jinghu1, 2, LI Weilian1, 2 (Yuanzineng kexue jishu, 2024)
Carrying out the experimental researches on the two-phase countercurrent behaviors in the flow unit of reactor core can provide sufficient theoretical supports for the smooth operation and emergency treatment of different forms of the reactor systems. In this research, the flooding phenomenon, the characteristics of flow parameters and formation mechanisms of parallel and countercurrent flooding instability of annular flow in rod bundle channel were analyzed, and the result indicates that one flooding cycle could be divided into the onset flooding region, the full flooding region and the whole liquid phase downstream region. The experimental conditions where the flow instability appeared in the rod bundle structure are in the flooding state according to the criterion from Wallis, but on the conversion line of flooding and not flooding state according to the criterion from Zapke and Alekseev. The experimental pressure drop changing with time was compared to the instability behaviors of annular flow, and the result shows that when the pressure drop reaches a local maximum, the high-speed photography captures the starting point of onset flooding region, and when the pressure difference reaches a local minimum, the starting point of whole liquid phase downstream region is seen in the field of view. According to the high-speed photographic image data processing, the parallel flow time, the countercurrent flow time and the overall cycle time were acquired and analyzed. When the liquid phase flow rate is lower than 0.1 m/s, the overall cycle time does not change significantly, and the parallel flow time is lower than the countercurrent flow time. When the liquid superficial velocity is within the range of 0.1-0.3 m/s, the overall cycle time decreases with the increasing gas superficial velocity, and the time ratio of the parallel and countercurrent flow time changes little. When the liquid superficial velocity is higher than 0.3 m/s, the time ratio increases with the increasing gas superficial velocity. The study on the micelle velocity for onset-flooding shows that when the liquid superficial velocity is lower than 0.2 m/s, the micelle velocity for onset-flooding is higher than the gas velocity. The value with which the micelle velocity for onset-flooding is higher than gas superficial velocity decreases gradually with the increasing liquid velocity. At some conditions with high gas velocity, the micelle velocity for onset-flooding is lower than the gas superficial velocity when the liquid superficial velocity is higher than 0.2 m/s. The formation mechanisms of parallel and countercurrent flooding instability depend upon the changing force of gas core and the effect of liquid gravity in different flooding regions.